Dynamic plasmid clustering in Bacteria: Influence of transcriptional activity and host cellular states - Guan-Lin Wang; Yi-Ren Chang (Biochemistry and Biophysics Reports, 2025)
High-copy-number (hcn) plasmids exhibit distinct spatial organization within bacterial cells, yet the underlying mechanisms and functional implications remain poorly understood. In this study, we systematically investigated the role of transcriptional activity and host cellular states in plasmid clustering. Using fluorescence imaging and quantitative analyses, we observed that transcriptional repression induced transient plasmid clustering, while transcriptional enhancement influenced clustering in a promoter-dependent manner. Additionally, environmental cues, such as glucose addition and growth phase transitions, modulate plasmid clustering independently of transcriptional activity. Glucose supplementation led to rapid plasmid dispersion, suggesting a link between metabolic state and plasmid dynamics. The switching between dispersed and clustered plasmid distributions as growth phase changes correlate with alterations in nucleoid organization. These findings highlight the complex interplay between transcription, nucleoid structure, and cellular state in regulating plasmid spatial distribution, providing new insights into bacterial genome organization and adaptation.